The Need for Development of Meaningful E-Module Teaching Materials to Optimize Mathematics Learning with a Focus on Critical Thinking Skills - Syahri, Andi Alim; Akib, Irwan; Sukmawati, Sukmawati (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This research aims to develop meaningful e-module teaching materials for Differential Equations course, with a focus on improving students' critical thinking skills. Using the Technological Pedagogical Content Knowledge (TPACK) framework, the e-module is designed to be interactive and flexible, allowing students to learn independently and in more depth. The research method involved student and lecturer needs analysis, observations, interviews, as well as a student survey to identify gaps in current learning. The results showed that the use of conventional teaching materials did not support the development of critical thinking skills. Therefore, the developed e-module includes various interactive features such as simulations, quizzes, and case studies to assist students in understanding abstract concepts in Differential Equations course. This e-module is expected to increase students' active involvement and provide a more meaningful learning experience. The novelty of this research lies in the integration of technology in a complex mathematics learning process, which has not been done much in previous studies.